2022
DOI: 10.1016/j.aninu.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Dietary nano-selenium alleviated intestinal damage of juvenile grass carp (Ctenopharyngodon idella) induced by high-fat diet: Insight from intestinal morphology, tight junction, inflammation, anti-oxidization and intestinal microbiota

Abstract: In recent years, high-fat diet (HFD) has been widely applied in aquaculture, which reduces the intestinal health of cultured fish. The current study evaluated the protective effects of nano-selenium (nano-Se) on intestinal health of juvenile grass carp ( Ctenopharyngodon idella ) fed with HFD. A total of 135 experimental fish were fed with a regular diet (Con), a HFD (HFD) and a HFD containing nano-Se at 0.6 mg/kg (HSe) for 10 weeks. The results showed that dietary nano-Se significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 82 publications
6
30
0
Order By: Relevance
“…Partially similar to these results, Fusobacterial, Bacteroidetes, Proteobacteria, and Firmicutes were the predominant phyla in this study. Our data was highly consistent with a study reported by Liu et al that found that Fusobacterial, Bacteroidetes, Proteobacteria, and Firmicutes are the main phyla in the gut of grass carp [ 67 ]. This evidence suggests that Fusobacterial, Bacteroidetes, Proteobacteria, and Firmicutes constitute the core flora of the grass carp.…”
Section: Discussionsupporting
confidence: 93%
“…Partially similar to these results, Fusobacterial, Bacteroidetes, Proteobacteria, and Firmicutes were the predominant phyla in this study. Our data was highly consistent with a study reported by Liu et al that found that Fusobacterial, Bacteroidetes, Proteobacteria, and Firmicutes are the main phyla in the gut of grass carp [ 67 ]. This evidence suggests that Fusobacterial, Bacteroidetes, Proteobacteria, and Firmicutes constitute the core flora of the grass carp.…”
Section: Discussionsupporting
confidence: 93%
“…2020; Liu et al. 2021, 2022). Consequently, there is an urgent need to solve the problems induced by HF diets in Grass Carp farming.…”
mentioning
confidence: 99%
“…However, Grass Carp farming in China has been encountering many serious problems, especially when high-fat (HF) diets are used (Gao et al 2011;Tang et al 2019). Dietary supplementation with excessive lipid (>9.6%) resulted in fatty liver syndrome (Du et al 2006), increased the liver oxidative stress response, and led to growth retardation and high mortality in Grass Carp (Zhao et al 2020;Liu et al 2021Liu et al , 2022. Consequently, there is an urgent need to solve the problems induced by HF diets in Grass Carp farming.…”
mentioning
confidence: 99%
“…The present study used Nile tilapia as a model, and we found that gossypol reduced the intestinal microbiota richness and diversity according to the high-throughput sequencing technology. Mounting evidence in fish have shown that the disruption of intestinal microbial homeostasis and the loss of bacterial diversity in fish may lead to metabolic disorders and disease. , For example, a high-fat diet reduced the gut microbiota richness and diversity and caused intestinal inflammation and oxidative stress in juvenile grass carp ( Ctenopharyngodon idella ) . Additionally, it has been found that the secondary metabolites from Anoxybacillus kamchatkensis had immunomodulatory properties on carp, Cyprinus carpio .…”
Section: Discussionmentioning
confidence: 77%
“…33,34 For example, a high-fat diet reduced the gut microbiota richness and diversity and caused intestinal inflammation and oxidative stress in juvenile grass carp (Ctenopharyngodon idella). 35 Additionally, it has been found that the secondary metabolites from Anoxybacillus kamchatkensis had immunomodulatory properties on carp, Cyprinus carpio. 36 According to our heat map analysis, the proportions of Anoxybacillus, Clostridiaceae, and Hyphomicrobium were significantly reduced in the ML and MH treatments.…”
Section: ■ Discussionmentioning
confidence: 99%